Wearing American Football helmets increases cervicocephalic kinaesthetic awareness in “elite” American Football players but not controls - McCarthy, Peter W. (Chiropr Man Therap, 2015)
BACKGROUND: While there have been investigations into the reduced neck injury rate of wearing protective helmets, there is little information on its effects on normal kinaesthetic neck function. This study aims to quantify the kinaesthetic and movement effects of the American football helmet. METHODS: Fifteen British Collegiate American football players (mean age 22.2, SD 1.9; BMI kg.m(2) 26.3, SD 3.7) were age and size matched to 11 non-American football playing university students (mean age 22.5, SD 3.6; BMI 24.3, SD 3.3 kg.m(2)). Both groups had their active cervical range of motion and head repositioning accuracy measured during neck flexion/extension using a modified cervical range of motion device and a similarly modified football helmet. RESULTS: Wearing helmets significantly reduced active cervical range of motion in extension in both groups (P = 0.007 and P = 0.001 Controls and American Footballers respectively). While both groups had similar repositioning when not wearing a helmet (flexion P = 0.99; extension P = 0.52), when wearing helmets, American football players appeared to be more accurate in relation to cervical kinaesthetic repositioning (ANOVA: P = 0.077: flexion effect size =0.84; extension effect size =0.38). CONCLUSIONS: Wearing American football helmets significantly reduces the active cervical range of motion in extension, along with a change in the neutral head position. American footballers have a greater accuracy in repositioning their head from flexion (potentially enhanced proprioception) when wearing a helmet. This finding might allow development of a simple objective test to help discern presence of minor concussive or cervical musculoskeletal injury on or off the field.